Supply chain management (SCM) practice - Augustine Paka, T. (Universiti Malaysia Sarawak, UNIMAS, 2006)
The objectives of this study are to investigate the factors causing poor Supply Chain Management (SCM) and effects of poor SCM. In this study, one company has been selected as a sample selection. A few methods were used in this study to figure out the problems or factors causing poor SCM and it effects to the company.